THE ASSOCIATION BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND CORPORATE FINANCIAL PERFORMANCE - Santoso, Adrian Himawan; Feliana, Yie Ke (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
Corporate Social Responsibility (CSR) is an emerging issue in the last two decades. Some people argue that the implementation of CSR increase corporate financial performance because CSR can bring sustainability for the firm. However, others argue companies should have better financial performance to do CSR. Previous studies show mixed results. This research aims to investigate the relationship between corporate financial performance and CSR. This study also examines the causality relationship that established between CSR and corporate financial performance. This study investigates 800 firms that listed on Indonesian Stock Exchange (IDX) in 2010 - 2012. Corporate financial performance is measured by two proxies, i.e. accounting based approach (ROA, ROE, and ROS) and stock-market based approach (stock return). While, CSR practices is measured by Corporate Social Disclosure Index (CSRDI) that developed base on Global Reporting Initiative (GRI) standard. The relationship between both of them was investigated by using multivariate linear regression. The causality relationships also consider the time difference between them, i.e. contemporaneous, lagging one period, and lagging two periods. Firm size and risk level are included in the regression as control variables. This study finds that (1) CSR provides positive impact on the financial performancein the contemporaneous and next 1 year time period; (2) financial performance that measured by ROA will influence positively CSR only for the next two years; (3) there is a significant positive relationship between firm size and CSR.These results suggest that CSR activities of Indonesia companies tend to be charity, so it only provides positive impact to the firm financial performance in no more than one year. In addition, it needs at least two years for profitable companies to realize their capability in CSR activities. Indonesian investors have not considered CSR as a key performance measure. Further, company size is a good predictor to the CSR practice.